Allelopathic Inhibition Effects of Myriophyllum spicatum on Growths of Bloom-Forming Cyanobacteria and Other Phytoplankton Species in Coexistence Experiments - Jeong, Seonah; Yang, Dongwoo; Joo, Sungbae; Park, Sangkyu (Journal of Plant Biology, 2021)
Many studies have attempted to find measures for control of cyanobacterial harmful algal blooms (cyanoHABs) caused by Microcystis, Anabaena, and other bloom-forming plankton species. We have investigated allelopathic inhibition of the submerged macrophyte Myriophyllum spicatum on four phytoplankton species of two taxonomic groups: Chlorophyta Selenastrum capricornutum, Scenedesmus obliquus, and cyanobacteria Microcystis aeruginosa (different strains for toxic, non-toxic, the North Han River originated (NHR) and colonies) and Anabaena circinalis. Inhibitions of unicellular cyanobacteria M. aeruginosa were over 50% for three consecutive days from the 3rd to the 5th day of the coexistence. M. spicatum even inhibited M. aeruginosa at a high initial concentration (1.1 mg L−1 Chl-a). Moreover, M. aeruginosa in a mixture of four phytoplankton species (S. capricornutum, S. obliquus, M. aeruginosa and A. circinalis) was selectively inhibited by M. spicatum. The inhibition of toxic, non-toxic, and NHR of Microcystis by M. spicatum were not significantly different. Colonial cyanobacteria strains were mostly not inhibited by M. spicatum.
Keywords: Allelopathy; Cyanobacteria; Harmful algal bloom; Microcystis aeruginosa; Myriophyllum spicatum; Phytoplankton